(untitled) (Raparin Journal of Humanities (RJH), 2024)
Violence in general, in all its forms, particularly verbal abuse, is one of the social and psychological problems facing educational institutions. Verbal abuse is widely spread and created educational problems, because in spite of this causing problems and disorders for the student and the effect of his/ her personality. Hence, the main purpose of this study is to identify the causes of verbal abuse toward students in public basic schools in Erbil city. For this purpose, the research, which used the quantity method, in the 125 basic schools of Erbil city, using samples in 10 schools, 381 students were assigned to the research criteria and as the research unit selected. As a result, the research has reached that "the impact of verbal violence, remains much more than other forms of violence, because the verbal violence had a direct effects on the student’s passion and mind, at the same time, the research demonstrate, now in a number of Erbil’s School, for controlling and organizing students, body violence has taken the place of verbal violence, and the results shows us that the verbal violence, among students itself, has increased in a considerable way.